PENGARUH SOSIALISASI PERPAJAKAN, KUALITAS PELAYANAN FISKUS, SANKSI PERPAJAKAN DAN PEMAHAMAN PERATURAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA DEMAK - Gardika Urwatul Wusqo, 13.05.52.0125; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2017)
Taxes have an important role as a source of revenue and income of the largest State to improve the welfare of the community. One of the taxpayers required to calculate, deposit and report the amount of tax payable is an individual taxpayer. Problems often arise in the community in influencing non-compliance or compliance with taxpayers of individuals or entities to fulfill their obligations to pay taxes due to lack of knowledge, and socialization that has not been comprehensive This study examines the effect of taxation socialization, tax service, tax sanction, and understanding of tax regulation on personal taxpayer compliance. This research was conducted at KPP Pratama Demak The type of data used in this study is primary data. Primary data source is obtained directly from the taxpayers KPP Pratama Demak as much as 100 sempel by using multiple linear regression techniques. The results showed that the socialization of taxation, fiscal services, tax sanctions, the understanding of tax regulations, have a positive and significant impact on taxpayer compliance of individuals in Demak.Keywords: Tax Socialization, Fiscal Services, Understanding of Tax Regulations